2021
DOI: 10.1186/s12885-021-08196-7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for people diagnosed with cancer: a systematic review of implementation outcomes

Abstract: Purpose Exercise is efficacious for people living after a cancer diagnosis. However, implementation of exercise interventions in real-world settings is challenging. Implementation outcomes are defined as ‘the effects of deliberate and purposive actions to implement new treatments, practices, and services’. Measuring implementation outcomes is a practical way of evaluating implementation success. This systematic review explores the implementation outcomes of exercise interventions evaluated unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 99 publications
(169 reference statements)
0
12
0
Order By: Relevance
“…38 Dropout is a general problem in many longitudinal trials involving exercise interventions. Pooling data from 37 studies in patients with cancer, Czosnek et al 47 reported a mean attrition rate of 38% with a range of 22%-56%. Joseph et al 48 systematically reviewed internet-based PA interventions, reporting a mean attrition rate of 22.3% with a range between 0% and 69%.…”
Section: Discussionmentioning
confidence: 99%
“…38 Dropout is a general problem in many longitudinal trials involving exercise interventions. Pooling data from 37 studies in patients with cancer, Czosnek et al 47 reported a mean attrition rate of 38% with a range of 22%-56%. Joseph et al 48 systematically reviewed internet-based PA interventions, reporting a mean attrition rate of 22.3% with a range between 0% and 69%.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cancer survivors report maintenance of exercise after treatment as challenging, and there is a need for implementation of exercise program in community setting for this population (16,26). The design of an exercise program can be essential for a successful implementation of exercise among cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based exercise groups for cancer survivors of mixed diagnoses and ages are safe, show physiologic and psychosocial bene ts and it is a valid setting to improve survivor care and promote adherence to PE (23)(24)(25). However, implementation of exercise interventions in real-world setting is challenging (26). There is a need for qualitative research to understand the contextual dimensions of group-based exercise for cancer survivors, which may be of importance in the application, implementation and dissemination of community-based exercise programs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…EE and DN developed the search strategy using a well-de ned systematic approach. (34) Relevant search terms and medical subject headings (MeSH) were identi ed by exploring the National Library of Medicine Database and, further, by reviewing a recent review of exercise intervention for cancer survivors (35). Speci c keywords and MeSH terms applied in the search include (but are not limited to) cancer, exercise, feasibility, etc., and implementation outcomes such as acceptability, adoption, appropriateness, practicality (See Additional File 1).…”
Section: Information Sources and Searchmentioning
confidence: 99%